2022
DOI: 10.3389/fcimb.2022.837019
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Exploring the Association of Entacapone, Gut Microbiota, and the Subsequent Side Effects in Patients With Parkinson’s Disease

Abstract: Background and AimsEntacapone, one of the most common drugs distributed among patients with Parkinson’s disease, is a peripherally acting catechol-O-methyltransferase (COMT) inhibitor that is used in addition to levodopa to control symptoms. However, there have been negative effects reported against entacapone, namely, gastrointestinal (GI) problems and drowsiness. In this pilot study, we aim to examine the hypothesis that the discomfort induced by entacapone might be originated from the shift of microbial com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…In addition, a substantial decrease in Faecalibacterium prausnitzii abundance coupled with a trend towards lower fecal butyrate associate with entacapone, a widely prescribed COMT inhibitor [ 198 ], but not with the analogues opicapone and tolcapone (the latter one has been withdrawn from the market for safety reasons) [ 108 , 199 ]. Other studies confirmed the alteration of taxa related to GI disorders and constipation upon entacapone intake [ 185 , 200 ]. In particular, Fu et al showed reduced Sellimonas , Lactobacillus , Faecalibacterium , Dorea , Intestinobacter and Blautia as well as augmented Eubacterium , Bifodobacterium and Christensenellacea _R-7_group in PD patients receiving entacapone combined with L-dopa versus those treated with L-dopa alone [ 200 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Biomarkers And Drug ...mentioning
confidence: 56%
See 1 more Smart Citation
“…In addition, a substantial decrease in Faecalibacterium prausnitzii abundance coupled with a trend towards lower fecal butyrate associate with entacapone, a widely prescribed COMT inhibitor [ 198 ], but not with the analogues opicapone and tolcapone (the latter one has been withdrawn from the market for safety reasons) [ 108 , 199 ]. Other studies confirmed the alteration of taxa related to GI disorders and constipation upon entacapone intake [ 185 , 200 ]. In particular, Fu et al showed reduced Sellimonas , Lactobacillus , Faecalibacterium , Dorea , Intestinobacter and Blautia as well as augmented Eubacterium , Bifodobacterium and Christensenellacea _R-7_group in PD patients receiving entacapone combined with L-dopa versus those treated with L-dopa alone [ 200 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Biomarkers And Drug ...mentioning
confidence: 56%
“…Other studies confirmed the alteration of taxa related to GI disorders and constipation upon entacapone intake [ 185 , 200 ]. In particular, Fu et al showed reduced Sellimonas , Lactobacillus , Faecalibacterium , Dorea , Intestinobacter and Blautia as well as augmented Eubacterium , Bifodobacterium and Christensenellacea _R-7_group in PD patients receiving entacapone combined with L-dopa versus those treated with L-dopa alone [ 200 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Biomarkers And Drug ...mentioning
confidence: 56%
“…A sophisticated model should be adapted if microbiome and constipation status are measured repeatedly in longitudinal follow-up studies. For those types of studies, PD medications such as entacapone which potentially lead to constipation ( Fu et al., 2022 ) should be considered a candidate mediator or time-varying confounder. A comparison of the microbial alteration between the constipation versus the non-constipation groups among PD patients would also be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…In particular COMT inhibitors, which have been associated with gut microbiome perturbations. 20,39 Last, the current study would benefit from other data sources, providing different types of gut microbiome profiling, including metabolomics and shotgun metagenomics for a more functional readout. Also, increased taxonomic resolution as potentially provided by shotgun metagenomics could further aid clinical trial design of probiotic studies using specific species or strains.…”
Section: Discussionmentioning
confidence: 99%